FIRST CLINICAL EXPERIENCE OF USING COLUMN FOR LPS-ADSORPTION OF TOXIPAK IN TREATMENT OF SEPSIS PATIENTS - L. L. Gendel; A. A. Sokolov; S. N. Gubanova; I. Yu. Adamova; P. A. Levashov (Вестник анестезиологии и реаниматологии)
Endotoxicosis is one of the main factors of the pathogenesis of multiple organic dysfunctions in gram-negative sepsis, induced by the accumulation of lipopolysaccharides - wall components of gram-negative bacteria. In vitro removal of them (LPS-adsorption) promotes better treatment outcomes in sepsis patients. Development and introduction of the Russian tools for LPS-adsorption becomes more crucial. Objective: to evaluate the efficiency and safety of the column of Toxipak for endotoxin removal, manufactured by POCARD Ltd. Materials and methods: 7 adult sepsis patients who had LPS-adsorption were included into the study. The changes of the following parameters were monitored in the patients: temperature, pulse, arterial pressure, respiration rate, central venous pressure, oxygen saturation, hourly rate of diuresis, oxygenation index was calculated, hematologic and biochemical blood parameters were tested as well as coagulation system rates, endotoxin level, C-reactive protein (CRP), procalcitonin, and interleukins (IL) 1, 6, 8. Criteria of the system inflammatory response and SOFA score were used for the comprehensive evaluation of clinical status. The adverse events, duration of stay in the intensive care ward and 18- and 24-day mortality were followed up during manipulations. Results: the studied column provided no negative effect on the cellular and biochemical composition, main parameters of clotting system and acid-base balance of blood. Its use resulted in the reduction of endotoxin (LPS) (by 64%), CRP (by 14%), IL-1 (by 38%) in blood, increase of oxygenation index, and renal function improvement. LPS adsorption promoted the reduction of clinical and laboratory signs of system inflammatory response, and severity of organ dysfunction (from 6.0 to 3.0 as per SOFA score) in patients with sepsis and septic shock. Conclusion: Toxipak column is safe and efficient for removal of endotoxins from blood.